Co‐microencapsulation of human umbilical cord‐derived mesenchymal stem and pancreatic islet‐derived insulin producing cells in experimental type 1 diabetes. Issue 2 (30th July 2020) - Montanucci, Pia; Pescara, Teresa; Greco, Alessia; Leonardi, Giulia; Marini, Luigi; Basta, Giuseppe; Calafiore, Riccardo
Abstract: Introduction: Post‐partum umbilical cord Wharton Jelly‐derived adult mesenchymal stem cells (hUCMS) hold anti‐inflammatory and immunosuppressive properties. Human pancreatic islet‐derived progenitor cells (hIDC) may de‐differentiate, and subsequently re‐differentiate into insulin producing cells. The two cell types share common molecules that facilitate their synergistic interaction and possibly crosstalk, likely useful for the cell therapy of type 1 diabetes (T1D). Materials and methods: Upon microencapsulation in sodium alginate (AG), hUCMS and hIDC were able to form cell co‐aggregates that looked well integrated and viable. We then grafted microencapsulated hUCMS/hIDC co‐aggregates into non‐obese diabetic/severe combined immunodeficient (NOD/SCID) mice, and observed an acquired ability of cells to produce and store hormones. Finally, we transplanted these biohybrid constructs into NOD mice with recent onset, spontaneous overt diabetes, observing a decline of blood glucose levels. Results: In vitro, we have shown that hUCMS inhibited proliferation of allogeneic polymorphonuclear blood cells from patients with T1D, while promoting expansion of FoxP3 + Tregs. Reversal of hyperglycemia in diabetic NODs seems to suggest that hUCMS and hIDC, upon co‐microencapsulation, anatomically and functionally synergized to accomplish two goals: maintain tracer insulin output by hIDC, while exploting the immunoregulatory properties of hUCMS. Conclusion: We have gathered preliminary evidence that the two adult stem cell types within AG microcapsules, may synergistically promote tracer insulin production, while "freezing" the autoimmune disease process, and help reversal of the recent onset hyperglycemia in a spontaneous, autoimmune rodent model of diabetes, the NOD mouse, with no need for pharmacologic immunosuppression.